A checklist of the deep sea fishes of the Levant Sea, Mediterranean Sea - Goren, Menachem; Galil, Bella S. (Zootaxa, 2015)
We list sixty five fish species collected at depths greater than 500 m in the Levant Basin, including 10 depth records. The Levantine bathyal ichthyofauna is characterized by its eurybathy, with an upper bathymetric boundary that permitted penetration of the shallow Gibraltar and Siculo-Tunisian sills, and a much lower bathymetric boundary than recorded for conspecifics elsewhere. The opportunistic and resilient ichthyofauna re-colonized recently the deep-sea following the last anoxic event ( 6 kyr), forming assemblages notably distinct from those in the western Mediterranean. The exploration and production of deep seabed hydrocarbons have raised the specter of severe direct impacts to the deep habitats. There is an urgent need for documenting the full extent of deep-sea biodiversity, and for providing information for the development of competent and pragmatic management plans and effective conservation policies.